Maxime Kamin, Représentations et poétiques du jeu dans la poésie française (langues d’oïl et d’oc) et latine du Moyen Âge (xiie-xiiie siècles) - Maxime Kamin (Perspectives Médiévales)
Historiography and literary criticism have long remained prejudiced against the place of games in Medieval culture. The reason for this is the tradition of mistrust surrounding playful activities, which were at best considered by ecclesiastical and civil authorities as silly or idle recreations, and at worst as a vain and sinful distraction likely to harm the social order. In line with Johan Huizinga’s and Roger Caillois’ heritage, we on the contrary put forward the idea that games can serve as apt metaphors for new insights into Medieval culture and be used to shape and envision its codes and values. In this respect, we aim to question the multivalent purpose of the game metaphor in Medieval literature. Opting for a cross-linguistic approach, we confront the various use of this metaphor through a corpus of works that put the spotlight on authors from different geographical and cultural areas. Our thesis thus intends to show that games can express and transmit moral, spiritual and other forms of knowledge in Medieval poetry.$ Certo, ecco la traduzione in italiano :